2016
DOI: 10.1038/srep39284
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of paclitaxel distribution in different tumor models assessed by MALDI mass spectrometry imaging

Abstract: The penetration of anticancer drugs in solid tumors is important to ensure the therapeutic effect, so methods are needed to understand drug distribution in different parts of the tumor. Mass spectrometry imaging (MSI) has great potential in this field to visualize drug distribution in organs and tumor tissues with good spatial resolution and superior specificity. We present an accurate and reproducible imaging method to investigate the variation of drug distribution in different parts of solid tumors. The meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…The observed apparent lack of drug also confirms the clinical practice for GIST patients with liver metastases that the best treatment option is a multidisciplinary one with continued TKI drug therapy and possibly surgical intervention (37). This result based on a small cohort of patient-derived tissues is in line with results from several MALDI-qMSI mouse studies on various chemotherapeutic drug agents in different cell line-based and patient-derived xenograft models (18,19,21,(38)(39)(40).…”
Section: Discussionsupporting
confidence: 76%
“…The observed apparent lack of drug also confirms the clinical practice for GIST patients with liver metastases that the best treatment option is a multidisciplinary one with continued TKI drug therapy and possibly surgical intervention (37). This result based on a small cohort of patient-derived tissues is in line with results from several MALDI-qMSI mouse studies on various chemotherapeutic drug agents in different cell line-based and patient-derived xenograft models (18,19,21,(38)(39)(40).…”
Section: Discussionsupporting
confidence: 76%
“…There are differences in the genetic and biological characteristics, clinical progression pattern, therapeutic responses, and prognoses among different tumor types; the distribution of paclitaxel in different tumors is also different [38]. Sensitivity analysis revealed that the study by Li et al [21] was a source of statistical heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…We then sorted out the ion signal intensities of alectinib from tumours before and after normalization with IS and evaluated the quantitative properties of the intensity data by comparing the results of LC‐MS/MS concurrently. Although the ion intensities of drugs and endogenous components from tissues have been related to LC‐MS/MS in previous reports (Reyzer et al, ; Burnum et al, ; Hankin and Murphy, ; Koeniger et al, ), comparison of ion intensity data from anti‐cancer drugs using whole tumour slices before and after normalization with IS has not previously been attempted (Giordano et al, ).…”
Section: Discussionmentioning
confidence: 99%